Karya Gambar dengan Teknik Cetak Stensil pada Siswa Kelas V Sekolah Dasar - Andini, Tiara; Anggraini, Dwi (Universitas Bengkulu, 2024)
This study describes the process of making and stencil printing technique drawings for class V C students of SDN 41 Kota Bengkulu. This type of research is qualitative with descriptive methods. The research instruments are observation guidelines, interviews and documentation. Data analysis is carried out by collecting data, reducing data, presenting data, and verifying data. Data validity techniques are through triangulation and member check. The results of this study are (1) in the pattern perforation step, groups 1 and 5 experienced obstacles because the image pattern was broken. Then, in the sponge formation stage, group 3 was the most creative because group 3 added tape to the end of the sponge so that it formed a handle. In the paint application step, groups 2, 3, and 5 mixed colors to get new colors. When touching the dye, group 3 experienced obstacles because they mixed the paint with water so that the paint overflowed onto the canvas. (2) The work of each group has elements of points, planes, shapes, colors, textures, light and dark, and space, but the element of spots is only found in the work of groups 2 and 3. The principles of fine art are unity, balance, rhythm, emphasis, proportion, and harmony. So it can be concluded that each group has created a work of art using stencil printing techniques according to the steps given. The work produced by each group has elements and principles of fine art.